Choroidal Vascularity Index in CHM Carriers - Mucciolo, Dario Pasquale; Giorgio, Dario; Lippera, Myrta; Passerini, Ilaria; Pelo, Elisabetta; Cipollini, Francesca; Sodi, Andrea; Virgili, Gianni; Giansanti, Fabrizio; Murro, Vittoria (Frontiers in Ophthalmology, 2021)
Purpose: To assess the choroidal structure using the Choroidal Vascularity Index (CVI) and analyse choroidal changes in choroideremia (CHM) carriers. Material and Methods: Female CHM carriers, genetically characterized, and a control group were recruited at the Eye Clinic of Careggi Teaching Hospital, Florence. The patients underwent a complete ophthalmic evaluation and retinal imaging. In particular, the Stromal Area (SA), Luminal Area (LA), Total Choroidal Area (TCA), CVI and Subfoveal Choroidal Thickness (SFCT) were calculated for each eye using Optical Coherence Tomography (OCT) examinations. Results: Twelve eyes of 6 CHM carriers and 14 eyes of 7 age-matched controls were analysed. The mean SFCT was 270.9±54.3μm in carriers and 281.4±36.8μm in controls (p=0.564); LA was 0.99±0.25mm2 and 1.01±0.13mm2 (p=0.172); SA was 0.53±0.09mm2 and 0.59±0.07mm2 (p=0.075) and TCA was 1.53±0.34mm2 and 1.69±0.19mm2 respectively (p=0.146). Mean CVI measured 64.03±3.98% in the CHM carriers and 65.25±2.55% in the controls (p=0.360). Conclusions: The CVI and CVI-related parameters (SA, LA and TCA) do not differ between CHM female carriers and controls. These findings reveal a preserved choroidal vasculature in eyes with RPE impairment and support the primary role of RPE in the pathogenesis of CHM disease.